Haloferax mediterranei, an Archaeal Model for Denitrification in Saline Systems, Characterized Through Integrated Physiological and Transcriptional Analyses - Torregrosa-Crespo, Javier; Pire, Carmen; Bergaust, Linda; Martínez-Espinosa, Rosa María (Frontiers in Microbiology, 2020)
Haloferax mediterranei (R4) belongs to the group of halophilic archaea, one of the predominant microbial populations in hypersaline environments. In these ecosystems, the low availability of oxygen pushes the microbial inhabitants towards anaerobic pathways and the presence of N-oxyanions favour denitrification. In a recent study comparing three Haloferax species carrying dissimilatory N-oxide reductases, H. mediterranei showed promise as a future model for archaeal denitrification. This work further explores the respiratory physiology of this haloarchaeon when challenged with ranges of nitrite and nitrate concentrations and at neutral or sub-neutral pH during the transition to anoxia. Moreover, to begin to understand the transcriptional regulation of N-oxide reductases, detailed gas kinetics was combined with gene expression analyses at high resolution. The results show that H. mediterranei has an expression pattern similar to that observed in the bacterial Domain, well-coordinated at low concentrations of N-oxyanions. However, it could only sustain a few generations of exponential anaerobic growth, apparently requiring micro-oxic conditions for de novo synthesis of denitrification enzymes. This is the first integrated study within this field of knowledge in haloarchaea and Archaea in general, and it sheds lights on denitrification in salty environments.